Development of a peanut-based mocha spread - Aunzo, Myra A.; Galves, Flor Crisanta F. (2000., 2000)
ABSTRACT Three formulations of peanut-based mocha spread were developed by adding different amounts of instant coffee and 19% sugar to peanut paste: formulation A used 6% instant coffee and 19% sugar, formulation B with 8% instant coffee and 17% sugar and formulation C with 10% instant coffee and 15% sugar. Equal levels of mocha flavoring and stabilizer were added to each formulation. The samples were evaluated by twenty-five consumer panelists under laboratory conditions for color, aroma, sweetness, mocha flavor and spreadability using 9-point hedonic scales. There were no significant differences at 5% level of significance in all attributes except for color. Formulation A received the highest mean score for color, aroma, sweetness, mocha flavor, and spreadability. However, formulation B received the highest mean score for overall acceptability. A mean score of 6.72 for formulation A was almost comparable to 6.76 of B. Formulation c received the lowest score of 6.28 since it was perceived to be bitter in taste. scores between 6.00 and 7.00 correspond to like slightly and like moderately, respectively, on a 9-point hedonic scale. The results indicated that a mocha spread using peanut paste as a base ingredient that is acceptable to consumers may be used.
Thesis (BSFT)-- University of the Philippines Diliman
Keywords: Peanut products